Types of cell death and apoptotic stages in Chinese Hamster Ovary cells distinguished by Raman spectroscopy. Issue 2 (3rd November 2017) - Rangan, Shreyas; Kamal, Sepehr; Konorov, Stanislav O.; Schulze, Hans Georg; Blades, Michael W.; Turner, Robin F. B.; Piret, James M.
Abstract: Cell death is the ultimate cause of productivity loss in bioreactors that are used to produce therapeutic proteins. We investigated the ability of Raman spectroscopy to detect the onset and types of cell death for Chinese Hamster Ovary (CHO) cells—the most widely used cell type for therapeutic protein production. Raman spectroscopy was used to compare apoptotic, necrotic, autophagic, and control CHO cells. Several specific nucleic acid‐, protein‐, and lipid‐associated marker bands within the 650–850 cm −1 spectral region were identified that distinguished among cells undergoing different modes of cell death; supporting evidence was provided by principal component analysis (PCA) of the full spectral data. In addition to comparing the different modes of cell death, normal cells were compared to cells sorted at several stages of apoptosis, in order to explore the potential for early detection of apoptosis. Different stages of apoptosis could be distinguished via Raman spectroscopy, with multiple changes observed in nucleic acid peaks at early stages whereas an increase in lipid signals was a feature of late apoptosis/secondary necrosis. Abstract : Raman spectroscopy successfully distinguished apoptotic and necrotic cell death in Chinese hamster ovary cells. The stages of apoptosis were also successfully identified; in particular, it was shown that the onset of apoptosis could be detected earlier than conventional annexin V staining. These results indicate that Raman spectroscopy is a promising tool for detecting cell state and the onset of cell death in bioreactor.